Juridical Study of the Role of the Regional Technical Implementation Unit for the Protection of Women and Children in Ensuring Legal Protection for Child Victims of Sexual Violence After the Birth of Law Number 12 of 2022 - Simbolon, Nanci Yosepin; Devi, Ria Sintha; Hamonangan, Alusianto; Yasid, Muhammad (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
Law Number 12 of 2022 concerning Crimes of Sexual Violence exists as the main and first special rule in dealing with Crimes of Sexual Violence and as a complement to Indonesian criminal law instruments used in law enforcement against various Crimes of Sexual Violence. One of the efforts to implement the Crimes of Sexual Violence Law is the establishment of Integrated Service Delivery in the regions through the Regional Technical Implementation Unit for the Protection of Women and Children. This study uses a normative juridical research type with a conceptual approach, which aims to find out the role of the  Regional Technical Implementation Unit for the Protection of Women and Children in accommodating every aspect of handling criminal acts of sexual violence, starting from efforts to prevent, handle, to recovery efforts for Crimes of Sexual Violence victims. The results of this study are: First, the Crimes of Sexual Violence Law is the main special regulation and a complement to Indonesian criminal law instruments for tackling sexual violence crimes. Second, the Crimes of Sexual Violence Law provides legal protection for victims of sexual violence by involving the Regional Technical Implementation Units for the Protection of Women and Children in provinces and districts/cities who have duties and responsibilities in terms of reporting, victim protection, investigations, and in terms of handling, protecting and victim recovery.